Genome-wide identification of Aux/IAA gene family and their expression analysis in Prunus mume - Cheng, Wenhui; Zhang, Man; Cheng, Tangren; Wang, Jia; Zhang, Qixiang (Frontiers in Genetics, 2022)
AUXIN/INDOLE ACETIC ACIDs (Aux/IAAs), an early auxin-responsive gene family, is important for plant growth and development. To fully comprehend the character of Aux/IAA genes in woody plants, we identified 19 PmIAA genes in Prunus mume and dissected their protein domains, phylogenetic relationship, gene structure, promoter, and expression patterns during floral bud flushing, auxin response, and abiotic stress response. The study showed that PmIAA proteins shared conserved Aux/IAA domain, but differed in protein motif composition. 19 PmIAA genes were divided into six groups (Groups Ⅰ to Ⅵ) based on phylogenetic analysis. The gene duplication analysis showed that segmental and dispersed duplication greatly influenced the expansion of PmIAA genes. Moreover, we identified and classified the cis-elements of PmIAA gene promoters and detected elements that are related to phytohormone responses and abiotic stress responses. With expression pattern analysis, we observed the auxin-responsive expression of PmIAA5, PmIAA17, and PmIAA18 in flower bud, stem, and leaf tissues. PmIAA5, PmIAA13, PmIAA14, and PmIAA18 were possibly involved in abiotic stress responses in P. mume. In general, these results laid the theoretical foundation for elaborating the functions of Aux/IAA genes in perennial woody plant development.